If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 28b + 6 = 16b Reorder the terms: 6 + 28b = 16b Solving 6 + 28b = 16b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-16b' to each side of the equation. 6 + 28b + -16b = 16b + -16b Combine like terms: 28b + -16b = 12b 6 + 12b = 16b + -16b Combine like terms: 16b + -16b = 0 6 + 12b = 0 Add '-6' to each side of the equation. 6 + -6 + 12b = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 12b = 0 + -6 12b = 0 + -6 Combine like terms: 0 + -6 = -6 12b = -6 Divide each side by '12'. b = -0.5 Simplifying b = -0.5
| 4x=3(10-x) | | 9x+21=5x+93 | | 4x=30-3x | | x-4/6=9 | | 115-3x=24x+22 | | 5a+y=180 | | 5=9+10y | | c=2*7.08*3.14 | | 9=2g-5 | | 7(2y+6)=4y+72 | | (2x-3)=(3x-5) | | 10x^6+8x^4=0 | | x=27+-2x | | x-10/x+2=7 | | -2.7=-1.3+0.7x | | x-(8x^(1/2))+4=0 | | 8/11(n+10)=64 | | -3x+12=9 | | 9-y=9 | | 15x-45+3x=18x+18-13 | | x+0.07x=16.05 | | 9x-1=8x+19 | | (9x+2)/5=4 | | (3x^2+2x-9)-(-3x+4)= | | -3-y=9 | | (3y/2a)/(8a^2y5/15y) | | 6x^2+2x-58=0 | | 2.3x-9.34=6.3 | | 4/17(x)=20 | | 3x-14=2x+19 | | -40-3x=14-10x | | 3-2(1/7) |